Assessment of the Potential for Reuse of Water in the Supply of the Metropolitan Region of São Paulo - Nascimento, José Freitas do; Ramos, Heidy Rodriguez; Côrtes, Pedro Luiz; Nascimento, Ana Paula Branco do (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2023)
The phenomenon of water scarcity has become a global problem, which among its main causes is the growth of the population that brings as a consequence an increasing demand for potable water, which is an admittedly limited resource. São Paulo, the greatest example of inequality in water distribution in Brazil with 22% of the population and only 1.6% of the country’s surface water, faced between 2014 and 2016 one of the biggest supply crises in its history, characterized mainly by the lack of rains. The work evaluated the current situation of reuse water use in the Metropolitan Region of São Paulo (MRSP) and interviews were carried out with specialists in the water resources sector, forming a representative tripod that involves the concessionaire of public water and sewage services, teaching institutions that study and research the topic and civil society entities responsible for managing the water resources that supply the city of São Paulo and 17 other municipalities in its surroundings. The study identified that much still needs to be done, necessarily counting on the active participation of the public power that has the largest structure to manage and encourage the practice of water reuse, that actions will be necessary to improve the legislation, so it is important that there is a permanent dialogue around the theme so that an alternative for water supply is available that meets the needs of society and collaborates with the sustainability of the planet.